GMPLS architecture and applications - Farrel, Adrian; Bryskin, Igor. (San Francisco : Elsevier/Morgan Kaufman, 2006)
The last two years have seen significant developments in the standardization of GMPLS and its implementation in optical and other networks. GMPLS: Architecture and Applications brings you completely up to date, providing the practical information you need to put the growing set of GMPLS-supported services to work and manage them effectively. This book begins by defining GMPLSs place in a transport network, leveraging your knowledge of MPLS to give you an understanding of this radically new control plane technology. An overview of GMPLS protocols follows, but the real focus is on what comes afterwards: in-depth examinations of the architectures underpinning GMPLS in real-world network environments and current and emerging GMPLS applications. This one-of-a-kind resource delivers immensely useful information for software architects, designers and programmers, hardware developers, system testers, and network operators--and also for managers and other decision-makers. + Written by two industry researchers at the forefront of the development of GMPLS. + Provides a practical look at GMPLS protocols for signaling, routing, link and resource management, and traffic engineering. + Delves deep into the world of GMPLS applications, including traffic engineering, path computation, layer one VPNs, point-to-multipoint connectivity, service management, and resource protection. + Explores three distinct GMPLS control plane architectures: peer, overlay, and hybrid, and explains the GMPLS UNI and NNIs. + Explains how provisioning challenges can be met in multi-region networks and details the provisioning systems and tools relied on by the GMPLS control plane, along with the standard MIB modules used to manage a GMPLS system.
Multiprotocol label switching -- An overview of transport networks -- From MPLS to GMPLS -- GMPLS signaling -- GMPLS routing -- Link management -- GMPLS and service recovery -- GMPLS and traffic engineering -- GMPLS path computation -- Constraint-based path computation -- Point-to-multipoint GMPLS -- Layer one virtual private networks -- Architectural models -- Provisioning systems -- GMPLS MIB modules.
Includes bibliographical references and index.
Keywords: Internet; Computer networks -- Management; Telecommunication -- Traffic -- Management; Electronic books